2022
DOI: 10.1002/ijc.34144
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of ivaltinostat combined with gemcitabine and erlotinib in patients with untreated locally advanced or metastatic pancreatic adenocarcinoma

Abstract: This phase I/II study evaluated the safety and efficacy of a new histone deacetylase (HDAC) inhibitor, ivaltinostat, in combination with gemcitabine and erlotinib for advanced pancreatic ductal adenocarcinoma (PDAC). Patients diagnosed with unresectable, histologically confirmed PDAC who had not undergone previous therapy were eligible. Phase I had a 3 + 3 dose escalation design to determine the maximum tolerable dose (MTD) of ivaltinostat (intravenously on days 1, 8 and 15) with gemcitabine (1000 mg/m 2 intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…A phase 2 study of traztuzumab, cetuximab and gemcitabine as a first line strategy in metastatic PDA showed disease stabilization in 27% of 33 patients. Cetuximab and traztuzumab combination has also been studied ( 39 ). Although the aforementioned studies were small, the durable activity of the antibody drug conjugate, Trastuzumab deruxtecan is well established.…”
Section: Discussionmentioning
confidence: 99%
“…A phase 2 study of traztuzumab, cetuximab and gemcitabine as a first line strategy in metastatic PDA showed disease stabilization in 27% of 33 patients. Cetuximab and traztuzumab combination has also been studied ( 39 ). Although the aforementioned studies were small, the durable activity of the antibody drug conjugate, Trastuzumab deruxtecan is well established.…”
Section: Discussionmentioning
confidence: 99%
“…ST-3595 ( Table 3 ), an inhibitor of hydroxamate-based histone deacetylase (HDAC), exhibited anti-proliferative and cytotoxic effects on PANC-1, AsPC-1, and Mia-PaCa-2 pancreatic cancer lines and human-derived pancreatic cancer cells [ 103 ]. HDACs are a class of enzymes that downregulate the expression of tumor suppression and differentiation genes through the removal of the acetyl group of histones, thus stabilizing the DNA-histone complexes, which induce chromatin compaction [ 143 ]. HDACs are usually overexpressed in several solid tumors, like pancreatic cancer, making them an essential target of anti-cancer therapy [ 144 ].…”
Section: Mixed (Combined) Inhibitors Of Pancreatic Cancermentioning
confidence: 99%
“…The anticancer effects of ivaltinostat ( Table 3 ), an intravenous hydroxamate-based pan-HDAC inhibitor previously referred to as CG200745, have been reported in various solid tumors like prostate cancer, cholangiocarcinoma, and pancreatic cancer [ 143 ], and it is said to induce cell death by modulating acetylation of p53, a tumor suppressor. In a complete report on a phase II clinical trial of HDACi-based chemotherapy for PDAC [ 143 ], Ivaltinostat with the gemcitabine/erlotinib regimen presented the results of Objective Response Rate (ORR 25%) and Disease Control rate (DCR 93.8%) (PR 25%, SD 68.8%) among 16 patients with an estimated OS and Progression-Free Survival (PFS) of 0.4 and 5.7 months, respectively. The ORR of 25% was much higher than the ORR of 8.6% seen in the former phase III study with a gemcitabine and erlotinib regimen.…”
Section: Mixed (Combined) Inhibitors Of Pancreatic Cancermentioning
confidence: 99%
“…The recently finished phase I/II trials combining ivaltinostat with gemcitabine and erlotinib treatment showed promising results regarding toxicity and patient survival. However, due to its single-arm design, results must be further validated (NCT02737228) [ 155 ]. The common side effects of epigenetic therapies are illustrated in Table 2 .…”
Section: Development Of Epigenetic Pdac Therapiesmentioning
confidence: 99%